Absence Causation and a Liberal Theory of Causal Explanation - Tang, Zhiheng (Australasian journal of philosophy, 2015)
For the framework of event causation-i.e. the framework according to which causation is a relation between events-absences or omissions pose a problem. Absences, it is generally agreed, are not events; so, under the framework of event causation, they cannot be causally related. But, as a matter of fact, absences are often taken to be causes or effects. The problem of absence causation is thus how to make sense of causation that apparently involves absences as causes or effects. In an influential paper, Helen Beebee offers a partial solution to the problem by giving an account of causation by absence (i.e. causation in which absences are supposed to be causes). I argue that Beebee's account can be extended to cover causation of absence (i.e. causation in which absences are supposed to be effects) as well. More importantly, I argue that the extended Beebeeian account calls for a major modification to David Lewis's theory of causal explanation, usually taken as standard. Compared to the standard theory, the result of this modification, which I shall call 'the liberal theory of causal explanation', has, among other things, the advantage of being able to accommodate causal explanations in which the explananda are not given in terms of events.